High-Resolution Environmental Magnetism Using the Quantum Diamond Microscope (QDM): Application to a Tropical Speleothem - Fu, Roger R.; Hess, Kimberly; Jaqueto, Plinio; Novello, Valdir F.; Kukla, Tyler; Trindade, Ricardo I. F.; Stríkis, Nicolás M.; Cruz, Francisco W.; Ben Dor, Oren (Frontiers in Earth Science, 2021)
Quantum diamond microscope (QDM) magnetic field imaging is a recently developed technique capable of mapping magnetic field sources in geologic samples at 1 micrometer resolution. Applying QDM imaging to speleothems can provide high resolution time series of detrital input into the cave environment, which, in turn, can yield useful paleoenvironmental information. Here we map the magnetic field in a speleothem from midwest Brazil over a 174 y timespan with annual to sub-annual resolution and perform backfield acquisition experiments to quantify changes in the magnetic grain population through time. We find that magnetic particles occur in highly enriched layers of 10-100 µm thickness that sample the same detrital source population. Combined with petrographic observations and electron microprobe mapping of Mg and Ca, we conclude that detrital enrichment in our sample is caused by drier conditions leading to slow or halted speleothem growth. This interpretation is compatible with oxygen isotopic data and implies that speleothem magnetism can be used to infer the past occurrence of drought and potentially quantify their duration. Future high-resolution magnetic imaging of speleothems may provide additional insight into the mechanism of detrital enrichment and establish their role as a proxy for local moisture and infiltration.